FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERIAN SUSU FORMULA PADA BAYI USIA 6 BULAN DI POSYANDU BOUGENVILLE JAKARTA BARAT TAHUN 2020 - Ipsan, Nathaza Caroline; Dewanto, Naomi Esthernita F (Fakultas Kedokteran Universitas Tarumanagara, 2021)
Exclusive breastfeeding rate in Indonesia for many years has been very low and there is an increased formula feeding practice. Formula feeding is influenced by many factors including, mother factors, baby factors and environment factors. This study aims to determine what factors are affecting formula milk feeding in infants aged 6 months at Posyandu Bougenville Jakarta Barat using a non random consecutive sampling method. This research is a descriptive study with a cross sectional design, gathering data from 146 respondents conducted specifically on mothers whose baby is 6 months old, use infant formula, and don’t give exclusive breastfeeding. Data collecting is done by answering questions on the questionnaire by online through a google form. The results obtained from 96 respondents who use infant formula show factors that affecting formula milk feeding are infant formula promotion (95%), baby’s health (49%), working mother (36%), lack of education of breastfeeding (6%) and mother’s health (2%). The act of formula feeding is multifactorial, this study recommend that every individual or organization involved should act and give support to exclusive breastfeeding and give a strict supervision and restriction regarding the use and promotion of formula milk especially for infants.